The Interaction of Dried Distillers Grains With Solubles (DDGS) Type and Level on Growth Performance, Health, Texture, and Muscle-Related Gene Expression in Grass Carp (Ctenopharyngodon idellus) - Abouel Azm, Fatma Ragab; Kong, Fanshuang; Wang, Xiaoyu; Zhu, Wenhuan; Yu, Haojie; Long, Xianmei; Tan, Qingsong (Frontiers in Nutrition, 2022)
The aim of this study was to estimate the possible synergetic effects of two levels of dietary DDGS from different sources (US-imported and native) on growth, health status, muscle texture, and muscle growth-related gene expression of juvenile grass carp. Four treatments of fish were fed with 4 isonitrogenous diets, namely native DDGS20, native DDGS30, US-imported DDGS20, and US-imported DDGS30 for 60 days. The US-imported DDGS30 group showed the better growth and feed efficiency. Additionally, we observed a significant increase in hepatopancreatic T-AOC and SOD in native DDGS groups. Moreover, raw muscle collagen increases considerably in the US-imported DDGS30 compared to the native DDGS30 group. In comparison with the native DDGS groups, the US-imported DDGS groups showed significantly decrease in all textural properties and fiber density, while increased fiber diameter. Dietary native DDGS inclusion significantly showed up-regulation of myog, myhc, and fgf6a expression in muscle, while down-regulation of the expression of myod, and myf5. Overall, US-imported DDGS30 had a beneficial influence on growth via regulating genes involved in myogenesis and hypertrophy, the formation of collagen, but had negative impacts on antioxidant capacity and cooked muscle texture.